PENGARUH KOMPETENSI, INDEPENDENSI, PROFESIONALISME, PENGALAMAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KUALITAS AUDIT (Studi Empiris Pada Kantor Akuntan Publik Di Pekanbaru, Padang Dan Medan) - Antonius Bonny Marbun; Restu Agusti; Azhari Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study is to get an empirical proof that competence, independence, professionalism, work experience, and organizational commitment can affect the audit quality. Population of this study is all auditors who work at Kantor AkuntanPublik (KAP) and registered in Direktori Ikatan Akuntan Publik Indonesia (IAPI) 2011 on Sumatera Area. Total sample of this study was 92 auditors from Kantor Akuntan Publik on Pekanbaru, Padang, and Medan. The method of data analysis in this study is using Multiple Linear Regression. Result of first hypothesis study showing that competence is having an effect on audit quality. The second hypothesis showing that independence can have a positive effect on audit quality. Next hypothesis is hypothesis three, which shows that professionalism is also have a positive effect to the audit quality. Fourth hypothesis shows that work experience can give a good effect on audit quality. And the last hypothesis result showing that organizational commitment can have a positive effect for the quality of audit. The result of calculation adjusted R²is 0,445. Thus, variable can explained that competence, time independences, auditors independences effect of 44,5%. And the rest of 56% is influenced by other variables which are not observed in this study.Keywords: Competence, Independence, Professionalism, Work Experience, Organizational Commitment and Audit Quality.